2006
DOI: 10.1136/oem.2005.021113
|View full text |Cite
|
Sign up to set email alerts
|

A higher risk of congenital anomalies in the offspring of personnel who served aboard a Norwegian missile torpedo boat

Abstract: Service aboard the MTB was associated with an increased risk of having children with congenital birth defects and having children that were stillborn. The causes of these findings are unknown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 18 publications
0
11
0
1
Order By: Relevance
“…19 Work on a specific FPB was found to be related to congenital malformations, but the causality was unclear. 1 Conflicting results have also been published regarding RF exposure and preterm births 2,13 and sex ratio. 2,3 RF electromagnetic exposure can have both thermal and non-thermal effects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…19 Work on a specific FPB was found to be related to congenital malformations, but the causality was unclear. 1 Conflicting results have also been published regarding RF exposure and preterm births 2,13 and sex ratio. 2,3 RF electromagnetic exposure can have both thermal and non-thermal effects.…”
Section: Discussionmentioning
confidence: 99%
“…Based on a cross-sectional questionnaire study of naval employees, a higher risk of congenital anomalies was found in offspring and stillborn babies in a subgroup that had been working aboard a specific fast patrol boat (FPB) that was equipped for electronic warfare. 1 All vessels in the RNoN are equipped with radar, transmitters and antennas. Aboard the smallest ships, like FPBs, the distance between personnel and the antennas is short.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Her ble data i stor grad basert på spørreskjema utfylt av personell i Sjøforsva-ret [33] og eksponeringsdata fra tidligere [26] og oppdaterte [34] målinger av radiofrekvente felt. Flere utfall ble studert, blant annet medfødte misdannelser [35], kjønnsratio [36], fertilitet [36,37] og reproduksjonsutfall hos kvinnelig personell [38].…”
Section: Eksempel 2 -Kvikksakenunclassified
“…An analysis of results from this survey showed that personnel who had served onboard a missiletorpedo patrol boat had a higher risk of congenital anomalies among their offspring than other personnel in the Navy [Magerøy et al, 2006]. Further investigation of the possible effects of radiofrequency fields on the reproductive ability of employees in the Navy was therefore of interest.…”
Section: Introductionmentioning
confidence: 96%